Peran Otonomi Daerah Untuk Meningkatkan Fungsi Pengel-olaan Keuangan Daerah Sebagai Instrumen Manajemen dalam Kebijakan Alokasi Belanja Pelayanan Publik - Suryo Pratolo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2011)
Regional autonomy that has long been the aspiration of the people had been executed after successfully fought for reform. After implemented, which should be considered is whether the regional autonomy that has been running for 4 yaers really can fullfil people's needs and create welfare for the people. We all know that the purpose of the existence of local government is creating public service. Public services must be created with the creative way through many aspect include regional financial management strategies. By using four independent variables: financing ability, mobilize funds ability, regional government independence, level of fiscal decentralization, and the level of flaypa per effect, researcher tested the role of regional autonomy by linking it to the influence of these four independent variables on the variable of public service expenditure allocation. By using a chow test resulted in a finding that the local government system and the personnel in the four years of implementation of regional autonomy tend looks not ready in achieving the vision of regional autonomy. Anotherfinding is that in general, regional autonomy has a role in improving the influence of financial management aspects on the allocation of expenditure on public services.